Exploring the Experience of EFL Learners on a Website for Language Learning to Practice Speaking English - Asi, Natalina; Fauzi, Iwan; Lestari, Ariesta; Mardiana, Dina; Amalia, Novika (Journal of English Teaching and Learning Issues, 2024)
In English language learning, web-based learning (WBL) provides a critical tool for practicing speaking skills, which requires synchronous interactions for effective learning. This study explores the efficacy of the "Harati Speaking" website, a web-based platform designed to enhance spoken English skills among Intermediate English learners. The research employs a quantitative descriptive method involving 64 second-year bachelor students from an Indonesian university's English Education Study Program. Data were gathered using the User Experience Questionnaire (UEQ), which evaluates six categories of user experience: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Results indicate a generally positive user experience, with specific strengths in the website's ability to provide an engaging and efficient learning environment. However, novelty and certain aspects of attractiveness and dependability received lower, though still satisfactory, ratings, suggesting room for design enhancements. Overall, the "Harati Speaking" website proves to be a valuable tool for practicing English speaking skills, contributing positively to the language learning process in a foreign language classroom. This study provides valuable insights into how such platforms can facilitate synchronous interactions essential for effective language learning. For future development of the "Harati Speaking" website, more innovative and engaging features could boost the web novelty, including gamification elements and interactive scenarios. By addressing these areas, future research can provide a more comprehensive understanding of the potential and optimization of web-based learning tools for English learning.